FRI0425 Analysis of cellular composition and cytokine expression in the subchondral bone marrow in ankylosing spondylitis. (15th June 2017) - Kenngott, EE; Bleil, J; Maier, R; Sieper, J; Syrbe, U
Abstract : Background: Ankylosing spondylitis (AS) is characterized by inflammation within the sacroiliac joints and at the spine including vertebral bodies and facet joints. In AS, bone destruction is followed by new bone formation leading to ankylosis of joints and syndesmophyte development. Histological studies of bone material from AS patients showed subchondral bone marrow changes, namely the transition of the bone marrow into granulation tissue which facilitates subchondral bone destruction but also promotes local bone formation [1, 2]. Currently, it is unclear what promotes the transition of the bone marrow into the granulation tissue. Objectives: The aim of this study was to look for changes in the subchondral bone marrow in joints from AS patients that may precede and promote transformation into granulation tissue. Therefore, we analyzed the cellular composition of the bone marrow and determined local cytokine expression at subchondral regions of AS facet joints. Methods: Facet joints were acquired from AS patients undergoing polysegmental correction surgery and compared to joints from autopsy controls. We performed immunohistochemical stainings to determine the number of T cells (CD3) and B cells (CD20), macrophages (CD68, CD163), monocytes (CD14), dendritic cells (DC; CD1a, DCsign) and myelopoietic cells (MPO). To correct for putative differences in fat cell content, software assisted image analysis was used to calculate the area of bone marrow covered by fat cells and the number of nucleated cells (DAPI) as well as myeloid cells. Cytokine expression was determined by mRNA in situ hybridization (TNF, IFNg) or immunohistochemistry (TGFβ, IL-10). Results: We observed no difference in the number of adaptive immune cells, i.e. CD3+ T and CD20+ B cells, between AS and control joints and found no difference in T/B cell aggregates. Furthermore, no difference in the number of macrophages (CD163+, CD68+) and DCs (CD1a+, DCsign+) was found. The only difference in cellular composition appeared to be a slight trend towards a higher percentage of myelopoietic MPO+ cells/DAPI+ cells in AS joints compared to control joints. The overall number of DAPI+ cells as well as the fat content of the bone marrow was not different between AS and control joints. Concerning cytokines, TNF mRNA expression was in general low but significantly increased (p<0.05) in AS versus control joints. No difference was found for IFNg. The number of TGFβ expressing cells was similar in AS and control joints while the number of IL-10 positive cells was decreased (p<0.01) in AS joints. Conclusions: The results show a shift from pro-inflammatory to anti-inflammatory cytokine expression within subchondral bone marrow sites in AS joints while no major change in the cellular distribution of the major leukocyte subsets is found. The shift in cytokine milieu may contribute to transformation of the bone marrow into granulation tissue. It would be interesting to determine the cellular source of local cytokines, such as of IL-10. References: Cruickshank B. Lesions of cartilaginous joints in ankylosing spondylitis. The Journal of pathology and bacteriology 1956;71(1):73–84. Bleil J, Maier R, Hempfing A, Sieper J, Appel H, Syrbe U. Granulation Tissue Eroding the Subchondral Bone Also Promotes New Bone Formation in Ankylosing Spondylitis. Arthritis Rheumatol 2016;68(10):2456–65. Disclosure of Interest: None declared